The coming changes in Irish local government - Johnston, W.H. (Statistical and Social Inquiry Society of Ireland, 1898)
The changes in Local Government proposed to be made by the Local Government (Ireland) Bill, which is now on the eve of the Committee stage, aptly illustrates some economic and social theories which may well be discussed by this society.
Read Tuesday, 19th April, 1898
Keywords: Local government; election; 314.15